Konsep Model Pengembangan Idea Management World Vision Indonesia - Hendra Hendra (Bina Nusantara University, 2013)
The purpose of this article is to compose a development model that can be used to manage the process of idea conversion, structure idea from tacit to be explicit, determine priority scale of an idea, accomodate idea discussion in a creative thinking, justify idea alignment with organization choices, and measure the impact of an idea management. The development model is shaped based on supported concept and tool of knowledge conversion, knowledge management cycle and its procedure, QCDSM objectives, organization alignment model, importance-urgency priority scale and six hats creative thinking. The result of this research is an integrated model with some designs of idea identification form and main functions of idea management application that are ready to be implemented.